Transformation efficiency of Arabidopsis thaliana ecotypes with differential tolerance to submergence stress - Mayra Santiago-Velasco; Erick Ortiz-López; Alexis Flores-Méndez; Blanca Estela Barrera-Figueroa; Edgar García-López; Julián Mario Peña-Castro (All Life, 2022)
Submergence stress in plants subjected to flooding is a significant issue in agriculture. Decades of previous research have elucidated many molecular and physiological responses of plants to this stress. Since Arabidopsis thaliana has been established as a model organism in this area of research, in this study, we started by replicating published results of seven sensitive and tolerant ecotypes of Arabidopsis to dark-submergence stress to assess its generalizability and consistency, adapted a leaf-damage index to quantify the progression of stress over time, and measured the recalcitrance of all those ecotypes to Agrobacterium transformation. By using photographic comparisons, median lethal time (LT50), and leaf-damage index, we ascertained that the order of tolerance reported by previous studies is robust enough to allow independent replications (Cvi-0 < Ita-0 < Bay-0 < Col-0 < Kin-0 < Lp2-6 < C24), supporting their consistency. We continued by testing the transformation recalcitrance of all seven ecotypes to three different Agrobacterium strains and identified C24 and Cvi-0 as the most suitable ecotypes useful in a transformation platform despite their low transformation frequencies (<0.1%). The results from this study can be useful in developing transgenic methodologies that enhance plant responses to stress and transitioning these methodologies from the laboratory to the field.